Strategi Internalisasi Nilai-Nilai Pendidikan Karakter Berbasis Budaya Jawa - Suci Rahayu; Shinta Tyas Prastisthita; Winarsih (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
Javanese culture-based character education is an effort to instill character rooted in Javanese cultural values so that students who have morals without leaving the noble value of the wisdom of the Indonesian nation are formed. The importance of character education at the elementary school level is as a strong foundation for students to face various negative things that come in students' lives. This research is based on the above background and formulated several problem formulations, including: 1) Definition of Internalization; 2) Character education concept; 3) The concept of Javanese cultural values; 4) A strategy for internalizing the values of Javanese culture-based character education at SDN 1 Karanganom; 5) Challenges and sustainability strategies for internalizing the values of Javanese culture-based character education at SDN 1 Karanganom. The purpose of this research is to describe the internalization of Javanese culture-based character education values at SDN 1 Karanganom. The method used in this study is a descriptive qualitative method. data was collected through observations, interviews with Principals, Teachers, Parents of students, and Students. The data analysis used the approach of J. Piaget's constructivism theory, Ki Hajar Dewantara's character education theory, and Albert Bandura's social cognitive theory. The results of this study show that the strategy used in the process of internalizing the values of Javanese culture-based character education at SDN 1 Karanganom through habituation activities, integration into the curriculum, and cultural preservation activities.